Reconstructing the Eemian to Middle Pleniglacial pedosedimentary evolution of the Baix loess-palaeosol sequence (Rhône Rift Valley, southern France): basic chronostratigraphic framework and palaeosol characterisation - Pfaffner, Nora; Kadereit, Annette; Karius, Volker; Kolb, Thomas; Kreutzer, Sebastian; Sauer, Daniela (Quaternary science journal, 2024)
Loess-palaeosol sequences (LPSs) are important archives of landscape evolution, recording alternating periods of geomorphic activity (dust deposition and slope processes) and landscape stability (soil formation). LPSs of the Rhône Rift Valley are located along a spatial climatic gradient from the mid-latitudes to the Mediterranean region. This position renders them extremely valuable archives for correlating LPSs in the European loess belt and the Mediterranean region. Despite this important function, Rhône Rift Valley LPSs have been little investigated. In this study, we aimed to narrow this knowledge gap, in a first step towards linking LPS-based mid-latitude and Mediterranean palaeoenvironmental reconstructions. We studied the ∼ 14 m thick Baix LPS located at the western edge of the Rhône Rift Valley near Valence. Here, we focus on the lower ∼ 7 m of the LPS, which comprises 12 of 19 soil horizons overall, and record regional palaeoenvironmental variations from the Eemian to the Middle Pleniglacial (∼ marine isotope stage (MIS) 5 to MIS 3). Our reconstruction is based on detailed field description, complemented by granulometry (10 cm vertical resolution), and micromorphological analyses. Luminescence screening of cut-out soil-sediment columns subsampled with ∼ 5 cm vertical resolution (126 subsamples over 7 m) provides a preliminary chronometry. The loess deposits of the Baix LPS are strongly calcareous and predominantly silty but also contain sandy and fine gravelly laminae typical of loess deposits subjected to slope-wash processes. From bottom to top, the investigated part shows three intensely pedogenised levels: (1) a basal sequence of reddish-brown Btg and Bt horizons of a thick Eemian Stagnic Luvisol (MIS 5e); (2) an early glacial yellowish-brown Bw horizon (MIS 5d-a); and (3) a yellowish-brown Bw horizon with large cone-shaped carbonate nodules in the associated underlying Bk horizon, interpreted as a truncated Middle Pleniglacial (MIS 3) Calcic Cambisol. The Baix LPS is in parts very similar to the Collias LPS ∼ 100 km further south but also exhibits differences, reflecting its position at the spatial climatic transition between the presently temperate and the Mediterranean zone.
Gesehen am 04.06.2024